Transcription of Myocyte enhancer factor-2 in adult Drosophila myoblasts is induced by the steroid hormone ecdysone. - Lovato, T.A.L.; Benjamin, A.R.; Cripps, R.M. (Developmental Biology, 2005)
The steroid hormone 20-hydroxyecdysone (ecdysone) activates a relatively small number of immediate-early genes during Drosophila pupal development, yet is able to orchestrate distinct differentiation events in a wide variety of tissues. Here, we demonstrate that expression of the muscle differentiation gene Myocyte enhancer factor-2 (Mef2) is normally delayed in twist-expressing adult myoblasts until the end of the third larval instar. The late up-regulation of Mef2 transcription in larval myoblasts is an ecdysone-dependent event which acts upon an identified Mef2 enhancer, and we identify enhancer sequences required for up-regulation. We also present evidence that the ecdysone-induced Broad Complex of zinc finger transcription factor genes is required for full activation of the myogenic program in these cells. Since forced early expression of Mef2 in adult myoblasts leads to premature muscle differentiation, our results explain how and why the adult muscle differentiation program is attenuated prior to pupal development. We propose a mechanism for the initiation of adult myogenesis, whereby twist expression in myoblasts provides a cellular context upon which an extrinsic signal builds to control muscle-specific differentiation events, and we discuss the general relevance of this model for gene regulation in animals.